2X^4Y^3-6X^3Y^4+3X^2Y^2等于什么啊?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 12:37:01
2X^4Y^3-6X^3Y^4+3X^2Y^2等于什么啊?2X^4Y^3-6X^3Y^4+3X^2Y^2等于什么啊?2X^4Y^3-6X^3Y^4+3X^2Y^2等于什么啊?=(x3y)(x^4-5x
2X^4Y^3-6X^3Y^4+3X^2Y^2等于什么啊?
2X^4Y^3-6X^3Y^4+3X^2Y^2等于什么啊?
2X^4Y^3-6X^3Y^4+3X^2Y^2等于什么啊?
=(x 3y)(x^4-5x^2y^2 4y^2) =(x 3y)(x^2-y^2)(x^2-4y^2显然原式不等于33 x^5 3x^4y-5x^3y^2-15x^2y^3 4xy
x+y/2+x-y/3=6,4(x+y)-3(x-y)=-20
{(x+y)/2+(x-y)/3=6 4(x+y)-3(x-y)=-20
4(x+y)-3(x-y)=-20,2/x+y+3/x-y=6
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
81/8*(-x-y)^6*(x-y)^3*4/9(x+y)^4*(y-x)^2
4x-3y/x-2y÷6y-8x/y-2x
(x+y)/2- x-y/2=6 3(x+y)=4(x-y)
x+y/3+x-y/2=6 4(x+y)-2(x-y)=40
(y-x)^4(x-y)^3+2(x-y)^6(y-x)
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=
(x+3y-4)(2x-y)
计算(2x-3y)(x+4y)-(3x+y)(x-2y)(2x-3y)(x+4y)-(3x+y)(x-2y)
因式分解(x-2y)(x-3y)+(x-4y)(x-5y)+(x-3y)(x-5y)+(x-2y)(x-4y)
x²/xy-x/y 3x/4x+y - x-2y/4x+y (1-y/y+x)÷x/y²-x²
(2x+y)(2x-3y)+x(2y+y) 2a(x-y)-4b(x-y)
计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x
因式分解 x-xy+3y-3x 2x+xy-y-4x+5y-6
1.((y+2x)(-2x+y)+4(x+2y)^2)/3y 2.(2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2)/2(x-y)^2